Analysis The Influence of Sharia Capital Market and Sharia Macroeconomic Variables on Indonesia’s Economic Growth - Miftahul Huda; Ahmad Suminto; Syaidatul Sa’diah; M. Kurnia Rahman Abadi (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2023)
The research aims to determine the effect of the Sharia capital market and Sharia macroeconomic variables on Indonesia's economic growth in 2017-2021 in the short and long term. The research uses quantitative methods, and the data used is secondary data from time series. The data analysis techniques used are the vector autoregression (VAR) and the vector error correction model (VECM). The results show that in the short term, the Indonesian Sharia Stock Index (ISSI), corporate sukuk, household consumption, and inflation do not have a significant effect on economic growth. The variables of the Indonesian Sharia Stock Index (ISSI) and corporate sukuk have a significant negative effect on GDP in the long run. Meanwhile, inflation has a significant positive effect on GDP in the long run. Household consumption does not affect GDP in the long run. Simultaneously, all variables, namely ISSI, corporate sukuk, household consumption, and inflation, have no significant effect on GDP. GDP responds positively to shocks that occur in ISSI, corporate bonds, and inflation. Meanwhile, household consumption has a negative response from GDP. The variable that has the largest contribution is GDP, household consumption, ISSI, and inflation, and the smallest contribution is shown by corporate sukuk.